2021
DOI: 10.3390/fermentation7040253
|View full text |Cite
|
Sign up to set email alerts
|

Domain Adaptation and Federated Learning for Ultrasonic Monitoring of Beer Fermentation

Abstract: Beer fermentation processes are traditionally monitored through sampling and off-line wort density measurements. In-line and on-line sensors would provide real-time data on the fermentation progress whilst minimising human involvement, enabling identification of lagging fermentations or prediction of ethanol production end points. Ultrasonic sensors have previously been used for in-line and on-line fermentation monitoring and are increasingly being combined with machine learning models to interpret the sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As per [3], FL can be categorized into Horizontal Federated Learning (HFL) [2,13], Vertical Federated Learning [14][15][16] and Federated Transfer Learning [17][18][19] based on the distribution characteristics of the data. Throughout this paper, we focus only on the HFL.…”
Section: Federated Learningmentioning
confidence: 99%
“…As per [3], FL can be categorized into Horizontal Federated Learning (HFL) [2,13], Vertical Federated Learning [14][15][16] and Federated Transfer Learning [17][18][19] based on the distribution characteristics of the data. Throughout this paper, we focus only on the HFL.…”
Section: Federated Learningmentioning
confidence: 99%
“…At present, the application of Federated Learning in market segments is also gradually developing [22][23][24]. However, there are few examples of literature on the application of Federated Learning to forecasting [25][26][27][28][29]; especially, the application of Federated Learning to the sustainable development research of e-commerce enterprise demand forecasting has not yet been found.…”
Section: Federated Learningmentioning
confidence: 99%